THE STYLE OF USING VEIL IN THE AGE OF GLOBALIZATION: Overview of Concepts and Practices - Darti Busni; Betria Zarpina Yanti; Doli Witro (Madura State Islamic Institute (Institut Agama Islam Negeri (IAIN) Madura), 2021)
Along with the times, some people see the veil as no longer a symbol of piety but instead follow trends or popular models, not to mention that the veil is only considered a necessity used at certain times like entangled criminal cases and attending court. On the other hand, some use the veil as following the concept stipulated in Islam, namely, an obligation that cannot be abandoned and not adhered to by certain times, conditions, and situations. This article aims to explain the veil concept in Islam and the form of practice in society. Methodically, this article uses a qualitative research method, a research library compiled in scientific articles and analyzed using the phenomenological-sociological approach. The results showed In essence, the veil’s actual use as a form of obedience to the sharia follows the veil concept taught in Islam, where women with veils are not limited to a specific time, situation, condition, and place. ABSTRAK Seiring perkembangan zaman, sebagian masyarakat ada yang memandang jilbab tidak lagi sebagai simbol ketakwaan, tapi lebih mengikuti tren ataupun model yang sedang populer, belum lagi jilbab hanya dinilai sebagai sebuah kebutuhan yang hanya digunakan di saat tertentu saja seperti terjerat kasus kriminal dan menghadiri sebuah pengadilan. Di sisi lain ada yang menggunakan jilbab sebagai sesuai dengan konsep yang ditetapkan dalam Islam yaitu sebagai sebuah kewajiban yang tidak bisa ditinggalkan dan tidak terpaut pada waktu, kondisi, dan situasi tertentu. Artikel bertujuan menjelaskan konsep jilbab dalam Islam dan bentuk praktek yang terjadi di masyarakat. Secara metode, artikel ini menggunakan metode penelitian kualitatif yang bersifat library research yang disusun dalam bentuk artikel ilmiah dan ditelaah dengan menggunakan pendekatan fenomenologis-sosiologis. Hasil penelitian menunjukkan pada hakikat yang sebenarnya dari penggunaan jilbab sebagai bentuk keta’atan terhadap syari’at inilah yang sesuai dengan konsep jilbab yang diajarkan dalam Islam yang mana perempuan berjilbab tidak terbatas pada waktu, situasi, kondisi, dan tempat tertentu.